Bilder mit Worten gemalt – zur Problematik der Audiodeskription als einer Form der Übertragung von Kunst - Kęsicka, Karolina (Studia Germanica Posnaniensia, 2014)
In this paper I shall analyze the audio description for purposes of fine arts as a special form of a multi-modal text. With reference to theoretical linguistic concepts of picture as a semiotic sign with iconic but also prototypical function (as a mental picture) this paper shows the differences between visual and verbal signs and attempts to clarify the definition of multimodal competence and their significance for audio describing. On that grounds we examine empirically the selected problems of audiodescription related to composition to demonstrate the difficulties in bringing the visual and verbal components together in one text.